Pengaruh Harga Transfer Dan Transaksi Hubungan Istimewa Terhadap Penghindaran Pajak Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021 - Sarah Ginting; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to test and analyze the effect of transfer prices and preferential relationship transactions on tax avoidance and to test and analyze the effect of profitability in moderating transfer prices and preferential relationship transactions on tax avoidance in infrastructure companies that are flattened on the indonesian stock exchange. The selection of samples in this study used the purposive sampling method with predetermined criteria, obtained by 23 companies for 6 years so that the total sample used was 138 data. The type of data used is secondary data obtained from the company's annual financial statements in the 2016-2021 period. This hypothesis is tested using descriptive statistical analysis, classical assumption test, multiple regression and moderation test, hypothesis test, namely t test and r analysis test. The results of this study show that partially the price of transfers and special relationship transactions has a negative and significant effect on tax avoidance. Profitability cannot strengthen but significantly affect transfer prices and preferential relationship transactions on tax avoidance